R-spondin2, a novel target of NOBOX: identification of variants in a cohort of women with primary ovarian insufficiency - Justine Bouilly; Isabelle Beau; Sara Barraud; Valérie Bernard; Brigitte Delemer; Jacques Young; Nadine Binart (BMC, 2017)
Abstract Background R-spondin2 (Rspo2) is a secreted agonist of the canonical Wnt/β-catenin signaling pathway. Rspo2 plays a key role in development of limbs, lungs and hair follicles, and more recently during ovarian follicle development. Rspo2 heterozygous deficient female mice become infertile around 4 months of age mimicking primary ovarian insufficiency (POI). The study aimed to investigate the regulation of RSPO2 and its potential involvement in pathophysiology of POI. Methods We cloned the RSPO2 promoter and performed transcriptional assays to determine if RSPO2 can be regulated by NOBOX, an ovarian transcription factor. Then, we evaluated 100 infertile women after obtaining a detailed history of the disease and follicle-stimulating hormone measurements, besides karyotype determination and fragile-X premutation syndrome investigation. All exons, intron-exon boundaries and untranslated regions of the RSPO2 gene were identified by sequencing, and the results were statistically analyzed. Results We found that RSPO2 can be regulated by NOBOX via the presence of NOBOX Binding Element in its promoter. Among 9 identified variants in POI women, 4 of them were equally homozygous, 4 have never been described (c.-359C > G, c.-190G > A, c.-170 + 13C > T and c.-169-8 T > A), only one c.557 T > C was predicted to alter a single amino acid in the RSPO2 protein (p.Leu186Pro). Conclusions RSPO2 is a novel target gene of the NOBOX key transcription factor, confirming its important role during the follicular growth in ovary. However, RSPO2 mutations are rare or uncommon in women with POI.